Designing the Topoppie MSME Business Model Using the Business Model Canvas Method - Zakiya Rahma Rizkiputri; Farda Hasun; Meldi Rendra (JTI: Jurnal Teknik Industri, 2025)
Topoppie, an MSME operating in the food and beverage sector in Bogor, Indonesia, faces challenges including low revenue, limited human resources, underutilised production capacity, and limited digital marketing initiatives. This study aims to evaluate and redesign Topoppie’s business model using the Business Model Canvas (BMC) framework, supported by SWOT analysis and financial simulation. Data were collected through interviews, observations, and literature review. Strategies were formulated using the TOWS matrix and further refined using the Value Proposition Canvas to improve alignment with customer needs. The redesigned business model introduces improvements in customer segments, value propositions, and distribution channels. Financial simulations project a 10% annual sales growth, resulting in a Net Present Value (NPV) of IDR 54,374,131 and a payback period of 1.3 years. This redesigned model is expected to enhance business sustainability and serve as a replicable reference for other MSMEs undergoing digital transformation. Keywords: Business Model Canvas, MSME Topoppie, Digital Marketing, Strategic Planning, Business Transformation, Financial Simulation